Effects of seated and standing cold water immersion on recovery from repeated sprinting - Leeder, J. D. C.; van Someren, K. A.; Bell, P. G.; Spence, J. R.; Jewell, A. P.; Gaze, D.; Howatson, G. (Journal of Sports Sciences, 2015)
This study investigated the effects of two different hydrostatic pressures (seated or standing) during cold water immersion at attenuating the deleterious effects of strenuous exercise on indices of damage and recovery. Twenty four male well-trained games players (age 23 ± 3 years; body mass 81.4 ± 8.7 kg: O2max 57.5 ± 4.9 ml/kg·min) completed the Loughborough Intermittent Shuttle Test (LIST) and were randomly assigned to either a control, seated cold water immersion or a standing cold water immersion (14 min at 14°C). Maximal isometric voluntary contraction, counter-movement jump, creatine kinase, C-reactive protein, interleukin-6 and delayed onset muscle soreness (DOMS) were measured before and up to 72 h following the LIST. All dependent variables showed main effects for time (P < 0.05) following the LIST, indicating physiological stress and muscle damage following the exercise. There were no significant group differences between control and either of the cold water immersion interventions. Seated cold water immersion was associated with lower DOMS than standing cold water immersion (effect size = 1.86; P = 0.001). These data suggest that increasing hydrostatic pressure by standing in cold water does not provide an additional recovery benefit over seated cold water immersion, and that both seated and standing immersions have no benefit in promoting recovery following intermittent sprint exercise.